2021
DOI: 10.3389/fpsyg.2021.743414
|View full text |Cite
|
Sign up to set email alerts
|

Perseverance of Effort and Consistency of Interest: A Longitudinal Perspective

Abstract: The present research, enlightened by the dynamic approach to language learning, aimed to trace the co-development of English as a foreign language (EFL) learners’ perseverance of effort (PE) and consistency of interest (CI), the two subdomains of grit, over a course time. To this aim, a factor of curves model (FCM) was employed to trace the covariance of the subdomains of L2 grit longitudinally over time; to explore how changes in PE and CI are affected by their initial states; and to what extent the variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Dong (2022) found that a fixed mindset correlated with anger, shame, hopelessness, boredom and anxiety. Wang, Shirvan et al (2021) stated that learners with a fixed mindset suffered more from boredom. Furthermore, learners with a fixed mindset also avoid challenging jobs assuming that their efforts will not be up to the task (Papi, Bondarenko et al, 2019).…”
Section: Language Mindsetsmentioning
confidence: 99%
“…Dong (2022) found that a fixed mindset correlated with anger, shame, hopelessness, boredom and anxiety. Wang, Shirvan et al (2021) stated that learners with a fixed mindset suffered more from boredom. Furthermore, learners with a fixed mindset also avoid challenging jobs assuming that their efforts will not be up to the task (Papi, Bondarenko et al, 2019).…”
Section: Language Mindsetsmentioning
confidence: 99%
“…Future studies on GRIT can be done with mixed methodology using no sex difference in GRIT. 12,16,22,28,29 The females have been consistent in aiming and being more self-controlled, contributing to higher GRIT. Their findings that contradict ours -the ones in favor of male sex and that of the lack of significant sex difference for GRIT -can be explained.…”
Section: Discussionmentioning
confidence: 96%
“… 12 That study also showed GRIT was the lowest among 25–34-year-olds and highest among those ≥65years and that GRIT “grows with age and that one learns from experience that processes such as quitting plans, shifting goals, and starting over repeatedly are not good strategies for success.” In another study among college students, GRIT score had a mild positive relationship with age. 22 A study among older adults found that GRIT was stable throughout older adulthood and that it may serve as a shielding factor that supports active adaptation to the developmental challenges of aging. 23 Another study conducted in Mexico among 9th and 12th-grade children revealed that the measured consistency of interest increases with relative age (age with respect to classmates) and drops to a lesser amount with absolute age (age at measurement), whereas the measured perseverance of effort increases with absolute age but not with relative age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic line of research into L2 grit continued with longitudinal research conducted by Wang et al (2021b) on language learners’ perseverance of efforts (PE) and consistency of interest (CI). This research was also enriched by the dynamic view of language education, and intended to assess the parallel growth of EFL learners’ two dimensions of L2 grit (i.e., PE and CI) over a flow of time.…”
Section: Review Of Lgcm In L2 Educationmentioning
confidence: 99%